UJI DAYA HAMBAT AIR PERASAN BUAH JERUK NIPIS (CITRUS AURANTIFOLIA S.) TERHADAP PERTUMBUHAN BAKTERI STAPHYLOCOCCUS AUREUS DI LABORATORIUM SEKOLAH TINGGI ILMU KESEHATAN SANTA ELISABETH MEDAN TAHUN 2025 - Mareanus Telaumbanua; Seri Rayani Bangun; Rica Vera Br Tarigan; Ruth Agree Kartini Sihombing (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Staphylococcus aureus is a gram-positive, round-shaped bacterium that resembles a grape. This bacterium produces toxins that can damage host cells, so it often shows resistance to some types of antibiotics. Alternative solutions based on natural ingredients are needed to inhibit the growth of Staphylococcus aureus bacteria, one of which is lime juice (Citrus aurantifolia S.), which has bioactive compounds such as flavonoids, alkaloids, and citric acid. The study aims to determine the ability of lime juice (Citrus aurantifolia S.) to inhibit the growth of Staphylococcus aureus bacteria in the Laboratory of the Santa Elisabeth Medan College of Health Sciences 2025. This research is a quantitative research using True experimental design with Post test only control group design. The results of the inhibition zone of lime juice with a concentration of 25% = 4.5 mm (weak), 50% = 6 mm (medium), 75% = 8.4 mm (medium), 100% = 12.2 mm (strong) and 0% = 0 mm with 5 repetitions. The results of the One Way ANOVA statistical test showed that the test of the inhibitory power of lime juice on the growth of Staphylococcus aureus showed a value (P = 0.000), which means (Ha) was accepted, namely there was an inhibitory power of lime juice on the growth of Staphylococcus aureus bacteria. This study can be concluded that lime juice (Citrus aurantifolia S.) has the ability to inhibit the growth of Staphylococcus aureus bacteria with various concentrations of lime juice containing secondary metabolites that have antimicrobial properties, namely Alkaloids and Flavonoids.